A 0.4 ​V, body-driven, fully differential, tail-less OTA based on current push-pull. (May 2020) - Faraji Baghtash, Hassan
Abstract: A tail-less, fully differential trans-conductance amplifier is presented in this paper. The proposed structure arranges the current push-pulls as the core amplifier blocks in an elaborate manner to achieve fully differential function with tail-less power optimized elements. The current push-pull structures reuse the bias current effectively to maximize the trans-conductance of block. The proposed OTA structure exploits this advantage to reduce the power consumption of proposed structure down to 0.3 ​μW. The Spectre Post-layout simulations with TSMC 180 ​nm CMOS technology file have been performed to validate the performance of the proposed ampliﬁer. The proposed ampliﬁer exhibits a DC gain of 81.37 ​dB and a phase margin of 59.2° at unity-gain frequency of 280.4 ​kHz for a 5 ​pF load capacitance. The proposed structure also delivers high CMRR and PSRR values of 126.2 ​dB and 79.1 ​dB, respectively. To investigate the performance of the design over process and temperature variations, the Monte Carlo and corner simulations are performed. The circuit biased with 0.4 ​V power supply.